Property Rights for Fishing Cooperatives : How (and How Well) Do They Work? - Aburto-Oropeza, Octavio; Leslie, Heather M.; Mack-Crane, Austen; Nagavarapu, Sriniketh; Reddy, Sheila M.W.; Sievanen, Leila (World Bank, Washington, DC, 2016)
Devolving property rights to local institutions has emerged as a compelling management strategy for natural resource management in developing countries. The use of property rights among fishing cooperatives operating in Mexico's Gulf of California provides a compelling setting for theoretical and empirical analysis. A dynamic theoretical model demonstrates how fishing cooperatives' management choices are shaped by the presence of property rights, the mobility of resources, and predictable environmental fluctuations. More aggressive management comes in the form of the cooperative leadership paying lower prices to cooperative members for their catch, as lower prices disincentivize fishing effort. The model's implications are empirically tested using three years of daily logbook data on prices and catches for three cooperatives from the Gulf of California. One cooperative enjoys property rights while the other two do not. There is empirical evidence in support of the model: compared to the other cooperatives, the cooperative with strong property rights pays members a lower price, pays especially lower prices for less mobile species, and decreases prices when environmental fluctuations cause population growth rates to fall. The results from this case study demonstrate the viability of cooperative management of resources but also point toward quantitatively important limitations created by the mismatch between the scale of a property right and the scale of a resource.